Eventos como estratégia de comunicação e marketing turístico na cidade de São Paulo - Carvalho, William Ladeia de (2021)
This research is about marketing communication with an emphasis on tourism marketing in the city of São Paulo, through the free public events Virada Cultural, Marcha para Jesus and Parada do Orgulho LGBT. The main objective is to study the contributions of these events to the São Paulo brand, which uses these events as a marketing strategy for the city. The study is based on theoretical and empirical research, complemented by interviews with the organizers of the aforementioned events. The main hypothesis is that the events' contribution to the São Paulo brand occurs due to the scope of events that deal with culture, evangelism and sexual diversity and that mobilize crowds at each edition, bringing visibility to the capital of São Paulo. These events are important communication tools and also have great media support nationwide, highlighting São Paulo as the right destination for the organization of big-events. The theoretical framework brings to light of the research authors who focus on themes that intersperse theories on marketing communication with an emphasis on marketing of places and tourist marketing, hospitality, event organization and the themes of this thesis: Culture – Virada Cultural, Evangelism – Marcha para Jesus and Sexual Diversity – Parada do Orgulho LGBT. Field research was carried out by the author's visits to events in the years 2018 and 2019 editions and interviews with event organizers in 2021. The have results shown that São Paulo, by hosting events that contribute to the dissemination of the destination, benefits all chain of commercial activities where the events take place, however, not all companies benefiting from the consumption of products and services support or sponsor the events, and without investments they tend to wither. The occupations caused by the events are political, allowing approaches related to inclusion, tolerance and entertainment for the people, it is also important to reinforce the brand São Paulo as a democratic and plural city. Some problems also arise in the organization of these events, which reverberate in the city's image in relation to infrastructure such as safety and hygiene arising from the mass of participants every year. The document resulting from this research allows us to observe the events beyond the common idea of a party, but of public occupations necessary for reflections on themes of extreme social relevance to contemporary dialogue(AU).